Geography, Health, and the Pace of Demo-Economic Development - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper investigates the impact of subsistence consumption and extrinsic and intrinsic causes of child mortality on fertility and child expenditure. It offers a theory for why mankind multiplies at higher rates at geographically unfavorable, tropical locations. Placed into a macroeconomic framework this behavior creates an indirect channel through which geography shapes economic performance. It is explained why it are countries of low absolute latitude where we observe exceedingly slow (if not stalled) economic development and demographic transition.
Keywords: J10; O11; O12; J13; 330; Demographic Transition; Geography; Health; Nutrition; Cross-Country Divergence